2013
DOI: 10.1371/journal.pone.0053586
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Adherence and Viral Suppression in a Nationally Representative Sample of HIV-Infected Adults on Antiretroviral Therapy for 6, 12 and 18 Months in Rwanda

Abstract: BackgroundGeneralizable data are needed on the magnitude and determinants of adherence and virological suppression among patients on antiretroviral therapy (ART) in Africa.MethodsWe conducted a cross-sectional survey with chart abstraction, patient interviews and site assessments in a nationally representative sample of adults on ART for 6, 12 and 18 months at 20 sites in Rwanda. Adherence was assessed using 3- and 30-day patient recall. A systematically selected sub-sample had viral load (VL) measurements. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 37 publications
5
68
3
Order By: Relevance
“…While the results of this study do not suggest that additional targeted adherence support for patients with depression would have improved HIV treatment outcomes in this cohort, it is noteworthy that all patients in this study were receiving care in Rwanda's National HIV programme, the success of which has been documented 39. Although our findings may be generalisable to other strong ART programmes with high adherence levels, in some settings adherence is most likely an important mediator between depression and attrition, and adherence-related support may represent an important intervention.…”
Section: Discussionmentioning
confidence: 57%
“…While the results of this study do not suggest that additional targeted adherence support for patients with depression would have improved HIV treatment outcomes in this cohort, it is noteworthy that all patients in this study were receiving care in Rwanda's National HIV programme, the success of which has been documented 39. Although our findings may be generalisable to other strong ART programmes with high adherence levels, in some settings adherence is most likely an important mediator between depression and attrition, and adherence-related support may represent an important intervention.…”
Section: Discussionmentioning
confidence: 57%
“…A global analysis of data from 48 countries, including those in North America, Europe, and SSA, found that in 2009 the United States had the highest mean CD4 + cell count at ART initiation (307 cells/µl) followed, remarkably, by Rwanda (287 cells/µl) [17,18]. Given this and other HIV programmatic scale-up successes in Rwanda [13,14,19], there are likely important lessons to be learned by comparing Rwanda’s experience with those of other countries in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…With an HIV prevalence of 3.0% [11], Rwanda has been scaling up access to HIV care since 2004, and the mature national programme has achieved more than 93% ART coverage [12] with high rates of retention [13] and medication adherence with viral suppression [14]. We therefore examined the proportion of persons enrolling in HIV care and initiating ART in the advanced stages of HIV infection among patients in Kigali, Rwanda, before and after the first expansion of national ART guidelines from a CD4 + threshold of 200 cells/µl to 350 cells/µl.…”
Section: Introductionmentioning
confidence: 99%
“…With a first-line HAART therapy or a salvage therapy, approximately 90% of HIV-infected patients have undetectable viral load. 13,14 However, some patients with sustained viral suppression were also found to have insufficient immunologic response, which may increase their risk of disease progression and death. 9,15 CD4 þ T-cell count serves as the major laboratory indicator of immune function in HIV/AIDS patients.…”
Section: Discussionmentioning
confidence: 99%